Evaluation of competencies and training objectives in the transition from Relational Advertising Strategy to the European Higher Education - Campillo Alhama, Concepción (Historia y Comunicación Social, 2014)
Evaluative research allows us to reorient the learning process of university students. Through this study evaluates the acquisition of skills, abilities and skills associated to the Strategy in Advertising and Public Relations students in Advertising and Public Relations degree from the University of Alicante, in the academic year 2012-2013. The results of this study show the future direction we should give this teaching-learning process, reinforcing the training goals less consolidated.